PENGARUH MODEL PICTURE AND PICTURE TERHADAP KEMAMPUAN MENULIS KALIMAT SEDERHANA PADA SISWA KELAS II SD UNISMUH MAKASSAR - Fitrah, Eky; Bahri, Aliem; Khaltsum, Ummu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low ability to write simple sentences in second-grade students of SD Unismuh Makassar. Based on initial observations, only 16 out of 46 students (34.78%) achieved the completion criteria. The main problems found include difficulties in choosing diction, composing subject-predicate structures, and low understanding of the use of capital letters and punctuation. This study aims to prove the effect of the Picture and Picture learning model on students' ability to write simple sentences. The research method used is quantitative with a pure experimental design (True Experimental Design) in the form of a Pre-test Post-test Control Group Design. The research sample consisted of 46 students divided into two classes, namely the experimental class (Picture and Picture Model) and the control class (Conventional Method/PBL). The data collection instrument was a simple sentence writing test whose validity and reliability were tested. Data analysis techniques used descriptive statistics and inferential statistics which included normality tests, homogeneity tests, N-Gain tests, and t-tests (Independent Sample T-Test). The results of the study showed that the average post-test score of the experimental class (88.69) was higher than the control class (83.69). Hypothesis testing through the Independent Sample T-Test produced a t-value of 6.313 with a significance of 0.001 <0.05, so H0 was rejected and H1 was accepted. The increase in students' abilities in the experimental class was strengthened by the average N-Gain of 0.62 which was included in the moderate category. The conclusion of this study shows that the use of the Picture and Picture model has a significant effect on improving the ability to write simple sentences of second-grade students of SD Unismuh Makassar because they are able to visualize abstract concepts into concrete ones.